THE DETECTION OF Ochetosoma heterocoelium (TRAVASSOS, 1921) (TREMATODA: DIGENEA: OCHETOSOMATIDAE) IN Chironius exoletus (LINNAEUS, 1758) (OPHIDIA: COLUBRIDAE) - Silva, R. J. Da [UNESP]; Rodrigues, R. R. [UNESP]; Stein, M. F. B. [UNESP]; Sipoli, G. P. M. [UNESP]; Pinhão, R. [UNESP]; Lopes, C. A. M. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 1999)
Two hundred and fifty-two specimens of Ochetosoma heterocoelium (Travassos, 1921) (Trematoda: Digenea: Ochetosomatidae) were detected in the mouth and esophagus of the snake Chironius exoletus (Linnaeus, 1758) (Ophidia: Colubridae) at the serpentarium of the Center for the Study of Venoms and Venomous Animals (CEVAP) of São Paulo State University (UNESP) in Botucatu, State of São Paulo, Brazil.
Keywords: Ochetosoma heterocoelium; Chironius exoletus; snakes; trematode